Contributions to Depatriarchalize Education: Feminist Training Experiences in Pandemics - Bonavitta, Paola (2022)
This work derived from the course “Feminist Knowledge and Practices in experiences of curricular integration” taught by two work teams located in Argentina: GAGES, belonging to the National University of San Juan (UNSJ), and El Telar, from the National University of Cordoba (UNC). This course was taught online through the Moodle platform via the Distance Education System (SIED) of the UNSJ, during May 2021, and was aimed at teachers and researchers of both institutions, with synchronous and asynchronous meetings distributed in five modules.The study started considering the university and its territory as a space for disputes, practices, and meanings. This article seeks to recognize, from teaching, extension, and research practices, the commitment to feminism as a way to decolonize higher education institutions.The questions guiding the paper are: Is it possible to depatriarchalize and decolonize universities? What role do university teachers and researchers play in the spaces we inhabit/transit? How do we contribute to stopping reproducing violence/inequality?The answers to these questions supposed to address the reflections collected in the course-workshop by the 51 people who attended the meeting. Then, students’ comments and proposals were analyzed.